Is the rigidity of the Spanish regional decentralization system leading to a soft budget constraint? - Toni Mora (European Regional Science Association (ERSA), 2005)
Recent contributions to the literature on public choice have examined the effects of regional fiscal balances and unsuitable decentralization mechanisms on the capability of regional governments to make expenditure decisions. We focus on Spanish regional case. Our results suggest that, given the negative relationship between additional improvements in tax revenue retention rates and the propensity to subsidize, the decentralization of revenues would be a more effective measure. Thus, the enhancement of the autonomous expenditure capacity of regional governments would be a more appropriate policy to adopt.
Keywords: 330